The Effect of Moringa oleifera Leaf Flour Substitution in Rations on Total Erythrocyte Count, Hemoglobin and Hematocrit Level in Boer Crossbreed Goat - Alfaruq, Fahmi Fadhillah; Qisthon, Arif; Sirat, Muhammad Mirandy Pratama (Faculty of Veterinary Medicine Universitas Brawijaya, 2024)
This study aimed to assess the impact of substituting Moringa oleifera leaf flour in the ration on the total erythrocyte count, hemoglobin levels, and hematocrit levels of Boer crossbred goats aged 4-12 months. The research was conducted from December 4, 2023, to January 17, 2024, at PERKASA Farms, Simpang Agung Village, Lampung Province. Laboratory analysis of total erythrocyte count, hemoglobin levels, and hematocrit levels was performed at the Laboratory of Pathology, Lampung Veterinary Disease Center. A Randomized Block Design was employed in this study, with three treatments and five groups, involving a total of 15 Boer crossbred goats, categorized based on body weight from smallest to largest. The treatments were as follows: P0=100% basal ration (60% cassava leaf and stem silage+40% concentrate); P1=95% basal ration+5% Moringa leaf meal; and P2=90% basal ration+10% Moringa leaf meal. Data were analyzed using ANOVA. The results of the study indicate that the mean values for total erythrocytes, hemoglobin levels, and hematocrit levels did not differ significantly (P>0.05) among treatments. The conclusion of this study was substituting Moringa oleifera leaf flour in the ration did not affect the total erythrocyte count, hemoglobin and hematocrit levels in Boer crossbred goats, indicating that Moringa leaf flour could be included in the ration up to 10%.